2020
DOI: 10.1186/s12929-020-00630-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistant ovarian cancer enhances its migration abilities by increasing store-operated Ca2+ entry-mediated turnover of focal adhesions

Abstract: Background: Among gynecological cancers, ovarian carcinoma has the highest mortality rate, and chemoresistance is highly prevalent in this cancer. Therefore, novel strategies are required to improve its poor prognosis. Formation and disassembly of focal adhesions are regulated dynamically during cell migration, which plays an essential role in cancer metastasis. Metastasis is intricately linked with resistance to chemotherapy, but the molecular basis for this link is unknown. Methods: Transwell migration and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
(71 reference statements)
0
27
1
1
Order By: Relevance
“…A study [ 61 ] showed that blocking store-operated Ca 2+ influx (SOCE) in MDA-MB-231 cells resulted in different localization of vinculin that caused slow focal adhesion turnover rate and strong cell adherence. Similarly, another study on mesenchymal-like chemoresistant IGROV1 ovarian cancer cells showed enhanced cell migration as a result of enhanced focal adhesion turnover mediated by SOCE [ 62 ]. It has been suggested that PMCA4b has the ability to decrease near-membrane Ca 2+ concentration in response to SOCE [ 63 ] that may explain, at least partly, the enhanced focal adhesion and reduced motility of the PMCA4b expressing melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study [ 61 ] showed that blocking store-operated Ca 2+ influx (SOCE) in MDA-MB-231 cells resulted in different localization of vinculin that caused slow focal adhesion turnover rate and strong cell adherence. Similarly, another study on mesenchymal-like chemoresistant IGROV1 ovarian cancer cells showed enhanced cell migration as a result of enhanced focal adhesion turnover mediated by SOCE [ 62 ]. It has been suggested that PMCA4b has the ability to decrease near-membrane Ca 2+ concentration in response to SOCE [ 63 ] that may explain, at least partly, the enhanced focal adhesion and reduced motility of the PMCA4b expressing melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the contribution of talin to cancer progression is timely. During this study ~ 670 more cancer-associated talin-1 point mutations have been added to the COSMIC database ( Supplementary Fig.S1) and there are recent studies discussing the connection between talin and cancer 23,[55][56][57][58] . The work we present here demonstrates an efficient and fast pipeline approach using bioinformatics tools to characterise future talin mutations identified in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…there are recent studies discussing the connection between talin and cancer 23,[55][56][57][58] . The work we present here demonstrates an efficient and fast pipeline approach using bioinformatics tools to characterise future talin mutations identified in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the contribution of talin to cancer progression is timely. During this study ~670 more cancer–associated talin–1 point mutations have been added to the COSMIC database (Fig.S1) and there are recent studies discussing the connection between talin and cancer 23, 5558 . The work we present here demonstrates an efficient and fast pipeline approach using bioinformatics tools to characterise future talin mutations identified in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%